Smart City Sebagai Salah Satu Alat untuk Mencapai Kota Berkelanjutan - Fridayani, Helen Dian; Rifaid, Rifaid (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2019)
Sustainable city is a city that designed by considering the impact on the environment, inhabited by population with a number and behavior that requires minimal support for energy, water and food from the outside, and produces less CO2, gas, air and water pollution. Moreover the national government envisions Indonesia2030which shallimplement the smart city towards sustainable development.Especially in Sleman Regency, the government is committed to make Sleman Regency as a Smart Regency in 2021. It could be shown in the vision of Sleman Regency which is The realization of a more prosperous Sleman community, Independent, Cultured and Integratede-governmentsystem to the Smart Regency in 2021”. This paper would like to analyze how the Sleman Regency implement the Smart city concept, and does the smart city concept can achive the sustainability city. The research uses the qualitative approach with in-deepth interview in examining the data, also the literature review. The result in this study reveals the following: firstly, from 2016-2019 Sleman regency has several applications to support the smart city implementation such as One Data of UMKM, Home Creative Sleman, Lapor Sleman app, Sleman Smart app, online tax app, e-patient, sleman emergency service, and Sleman smart room. Second, there are many elements in smart cities that are very important for smart government, smart life, smart economy, smart society, and smart environment. However, in supporting to support the realization of smart cities, not all aspects must be implemented properly to achieve a managed city, components related to smart environment cannot be implemented properly in Sleman Regency. There are still many problems regarding environmental problems such as the development of the construction of hotels and apartments that do not heed the environment, incrasing the populations, the limitations of green open space.